The Uses and Abuses of Inequality. Issue 2 (3rd April 2019) - Ghosh, Jayati
Abstract: Social inequalities obviously affect human capabilities and are undesirable from a welfare standpoint. But they may actually be useful for particular growth trajectories, by creating segmented labour markets that reduce production costs. Some patterns of growth may rely on such inequalities and thereby accentuate and perpetuate them. In extreme cases, "modernising" capitalism, instead of destroying traditional forms of social oppression and discrimination, can strengthen pre-existing social inequalities. Two examples from India illustrate this: the significance of unpaid and underpaid care work that both relies upon and reinforces gender-based inequalities; and the persistence of dehumanising forms of work such as manual scavenging and unprotected sanitation work, that rely upon caste discrimination. To avoid the most regressive and oppressive socio-cultural tendencies of the past being strengthened by the operations of capitalism, policy interventions need to reiterate the core principles of ensuring human freedom and dignity in the economic sphere as well.